25-Gauge Catheter as a Surrogate to Anterior Chamber Maintainer in Trabeculectomy. (August 2021) - Kusabara, Alessandra A.; Kasahara, Niro
A flat anterior chamber (AC) is a distinctive feature in status post vitrectomy eyes during trabeculectomy. The use of AC maintainers is useful to help prevent this peroperative situation. We herein describe the surgical technique using a 25-gauge intravenous catheter as a surrogate to conventional AC maintainers. A potential advantage of this approach is the low cost in the current economic environment with limited health restraints.